Avaliação de técnicas de compressão de sinais Para o fronthaul - BRITO, Flávio Mendes de (Universidade Federal do Pará, 2020)
The growing data demand of mobile networks has motivated the creation and evolution of architectures aiming to supply such transfer requirements. To meet these requirements, a number of challenges need to be met, including data transfer at the link between the Base Station Unit (BBU) and the Remote Radio Head (RRH). Known as fronthaul, this link requires high speed information transfer and one method that allows to tranfer more data using the same rate is data compression. Therefore, this study aimed to evaluate different techniques used in fronthaul data compression. Initially, the efficiency of some quantizers such as the scalar quantizer (SQ), twodimensional vector (VQ) and the Trellis Coded Quantization (TCQ) was verified. The analysis consists of combining these quantizers with resampling, Block Scaling and Huffman coding. In both analyzes, it was found that the system using TCQ as quantizer obtained the best relationship between Error Vector Magnitude (EVM) and computational cost, offering an EVM lower than the scalar quantizer and a computational cost lower than the vector quantizer.